Observations on the Infection by Kudoa sp. (Myxozoa, Multivalvulida) in fishes caught off Rio Grande, Rio Grande do Sul State, Brazil - Jorge Costa Eiras; Joaber Pereira Júnior; Aurélia Saraiva; Cristina Faria Cruz (Acta Scientiarum: Biological Sciences, 2016)
It is reported the parasitization of Kudoa sp. (Myxozoa, Multivalvulida) within the somatic muscles of the fish Odontesthes bonariensis (Valenciennes, 1835), Micropogonias furnieri (Desmarest, 1823) and Mugil liza Valenciennes, 1836, captured off Rio Grande, Rio Grande do Sul State, Brazil. Other species of fish caught at the same place were not infected. The parasites formed elongated plasmodia inside the muscle fibres. Myoliquefaction or any host tissue reaction were not observed. The morphological and morphometric features of the spores are described, the parasites are compared with other Kudoa species, and the importance of the infection is discussed.